PERSEPSI PENDENGAR TERHADAP PROGRAM REVIEW KELAKUAN TEMAN ATAU TETANGGA RADIO EBS FM DENGAN TOPIK PERMASALAHAN UANG DAN HUTANG (The Commercium, 2023)
This study aims to determine the perception of EBS FM Radio listeners on social problems of money and debt in the Review of Behavior of Friends or Neighbors program based on differences in background, experience, socio-culture, age, and work of informants. The Friends or Neighbors Behavior Review Program is made according to the "needs and wants" of listeners, one of which discusses social phenomena that often occur in the younger generation, namely social problems of money and debt. The type of research used in this study is qualitative descriptive research to understand the phenomena experienced by research subjects systematically with data collection carried out through observation, documentation and interviews of resource persons in the field obtained through purposive sampling techniques. The concept of perception to find out how listeners perceive social problems of money and debt in the Friends or Neighbors Behavior Review program. The results of various listeners' perceptions of the social problems of money and debt were obtained as a forum to accommodate listeners' complaints that discussed the social problems of money and debt in accordance with the reality of life and in accordance with the phenomenon of Generation Z and Millenials problems in Surabaya seen from motivation, attention, and attitudes that affect the formation of listener perceptions and are supported by stimulus factors, experiences, events and relationships. The conclusion of this study is that listeners' perceptions of money and debt problems on EBS FM Radio's Friends or Neighbors Behavior Review program had a positive impact and were well received.